Konstrusi Makna Legalisasi Ganja Bagi Anggota Komunitas Lingkar Ganja Nusantara - Dede Mulyana Sidik Fermana; Mayasari Mayasari; Ana Fitriana Poerana (Peneliti.net, 2022)
This study aims to describe more deeply about the construction of the meaning of marijuana legalization for the LGN community. The mainstream culture that considers marijuana as something dangerous and criminal makes this movement contrary to existing values ​​and norms. The issue of marijuana legalization promoted by the Lingkar Ganja Nusantara (LGN) organization has a different and distinctive movement in society. The research method used in this study is a descriptive qualitative approach. Through this approach, the authors make observations and dig deeper information through interviews with active members of LGN as research subjects. The approach used to see the phenomenon of marijuana legalization is a phenomenological study. Data collection techniques carried out by the author, namely qualitative observation, qualitative interviews, and documentation. This study shows that the movement for legalization of marijuana by LGN in the community has led to other views, education and advocacy on the use of the cannabis plant that was conveyed by LGN is an alternative bargaining for health services from the cannabis plant. Therefore, LGN in the movement's forum demands the holding of cannabis research. LGN hopes that after the research, there will be a change in views about cannabis in the community so that cannabis can be used for its benefits for the wider community.